Systemic venous anomalies in the Middle East - Corno, Antonio F.; Alahdal, Sami A.; Das, Karuna M. (Frontiers in Pediatrics, 2013)
INTRODUCTION Systemic venous anomalies are quite rare and can be associated with congenital heart disease requiring surgery. MATERIALS AND METHODS All consecutive patients (pts) undergoing surgery for congenital heart defects were retrospectively analyzed for presence of systemic venous anomalies: a) persistent left superior vena cava (PLSVC) b) inferior vena cava (IVC) interruption c) retro-aortic innominate vein. RESULTS From 9/2010 to 5/2012 155 pts, median age 7 months, mean age 1.3 years (3days-50years), median weight 4 kg, mean weight 7.2 kg (0.6-110kg) underwent congenital heart surgery. Twenty-nine systemic venous anomalies were identified in 28/155 patients (=18.1%). PLSVC was present in 21 pts (=13.5%), median age 4 months, mean age 2.7 years (3days-22years), median weight 6 kg, mean weight 10.1 kg (2.4-43.0 kg). IVC interruption was identified in 5 pts (=3.2%), median age 2 months, mean age 5.4 years (30days-26years), median weight 3.7kg, median weight 17 kg (2.3-68.0kg). Retro-aortic innominate vein was diagnosed in 3 pts (=1.9%), median age 5 years, mean age 3.7 years (10months-5years), median weight 12 kg, mean weight 10.1 kg (4.5-14kg). Complete pre-operative diagnosis was obtained in 14/28 (=50%) pts with echocardiography and in other 8/28 (=28.6%) only after computed tomography (CT) scan, for a total of 22/28 (=78.6%) correct pre-operative diagnosis. In 6/28 (=21.4%) patients the diagnosis was intra-operative. Total incidence of systemic venous anomalies was 18.1% (vs 4% in the literature, P=0.0009), with presence of PLSVC = 13.5% (vs 0.3-4.0%, respectively P=0.0004 and P=0.0012), IVC interruption = 3.2% (vs 0.1-1.3%,N.S.), and retro-aortic innominate vein = 1.9% (vs 0.2-1%,N.S.). CONCLUSIONS Our study showed an incidence of systemic venous anomalies in Middle Eastern pts with congenital heart defects higher than previously reported. In 78.6% of pts the diagnosis was correctly made before surgery (echocardiography or CT scan), with 21.4%